Determination of multiaxial stress rupture criteria for creeping materials: A critical analysis of different approaches. (20th February 2023) - Zhang, Kun; Tan, Jian-Ping; Sun, Wei; Nikbin, Kamran; Tu, Shan-Tung
Highlights: Factors affecting different methods for the determination of MSRC are analyzed. Principles in the determination of MSRC are recommended. The factor, α, is strongly dependent on the operative creep failure mechanism. A relation exists between multiaxial factor, α, and damage tolerance parameter, λ . Abstract: Materials in engineering applications are rarely uniaxially-loaded. In reality, failures under multiaxial loading has been widely observed in engineering structures. The life prediction of a component under multiaxial stresses has long been a challenging issue, particularly for high temperature applications. To distinguish the mode of failure ranging from a maximum principal stress intergranular damage to von Mises effective stress rupture mode a multiaxial stress rupture criterion (MSRC) was originally proposed by Sdobyrev and then Hayhurst and Leckie (SHL MSRC). A multiaxial-factor, α, was developed as a result which was intended to be a material constant and differentiates the bias of the MSRC between maximum principal stress and effective stress. The success of the SHL MSRC relies on accurately calibrating the value of α to quantify the multiaxial response of the material/geometry combination. To find a more suitable approach for determining MSRC, the applicability of different methods are evaluated. Given that the resulting analysis of the various approaches can be affected by the creep failure mechanism, principles in the determination of MSRC with and without using continuum damage mechanics approaches are recommended. The viability of uniaxial material parameters in correlating with α through the analysis of available data in literature is also presented. It is found that the increase of the uniaxial creep damage tolerance parameter λ is accompanied by the decrease of the α –value, which implies that the creep ductility plays an important role in affecting the multiaxial rupture behavior of materials. Graphical abstract: Image, graphical abstract